PERUBAHAN DAN RESTRUKTURISASI DALAM ORGANISASI - Hadian , Dedi (Majalah Bisnis & IPTEK, 2021)
Today many world-class business organizations have experienced difficulties faced constantly changing business environment, business planning difficult implications and implementation of business programs formulated to effectively and rationally difficult to achieve. Changes in the organization involves a restructuring of human resources, a source of functional, technological capabilities and organizational capabilities. Under these conditions, efforts to reduce internal costs through changes in the organization of the hierarchical- mechanistic-autocratic-confrontational towards network-organismic-participatory-coexistence are the natural consequences that require high motivation of the stakeholders and shareholders. Keywords: organizational structure; organizational restructuring; motivation